Pharmacokinetic study with computational tools in the medicinal chemistry course - Monique Araújo de Brito (Universidade de São Paulo, 2011)
To improve the teaching-learning process in the Medicinal Chemistry course, new strategies have been incorporated into practical classes of this fundamental discipline of the pharmaceutical curriculum. Many changes and improvements have been made in the area of medicinal chemistry so far, and students should be prepared for these new approaches with the use of technological resources in this field. Practical activities using computational techniques have been directed to the evaluation of chemical and physicochemical properties that affect the pharmacokinetics of drugs. Their objectives were to allow students to know these tools, to learn how to access them, to search for the structures of drugs and to analyze results. To the best of our knowledge, this is the first study in Brazil to demonstrate the use of computational practices in teaching pharmacokinetics. Practical classes using Osiris and Molinspiration were attractive to students, who developed the activities easily and acquired better theoretical knowledge. Para melhorar o processo ensino-aprendizagem no curso de Química Medicinal novas estratégias estão sendo incorporadas às aulas práticas desta disciplina fundamental do currículo farmacêutico. Muitas mudanças e melhorias vêm marcando a área de química medicinal e por isso é importante que os alunos sejam colocados nestas novas abordagens na área, com a utilização de recursos tecnológicos. As atividades práticas foram direcionadas para a avaliação dos dados químicos e físico-químicos de fármacos que influenciam as propriedades farmacocinéticas com o auxílio de técnicas computacionais. Os objetivos foram permitir aos alunos conhecer essas ferramentas, saber como acessá-las, procurar as estruturas de fármacos e analisar os resultados. Este é o primeiro estudo publicado no Brasil que apresenta aula prática computacional sobre o tema farmacocinética. As aulas práticas utilizando os servidores Osiris e Molinspiration foram atraentes para os alunos, que desenvolveram as atividades com maior facilidade e sedimentaram o conhecimento teórico adquirido em sala de aula.